Lyme disease presenting with erythema migrans: First reported case in a returning traveler to the Kingdom of Saudi Arabia - Mazin Barry (IDCases)
Lyme disease is a tick-borne disease caused by Borrelia burgdorferi that often presents with a solitary rash at the bite site, which may have central clearing, giving a “Bull’s-eye” appearance, otherwise known as erythema migrans (EM). The disease is endemic in North America and Europe; however, cases have been reported in non-endemic areas in returning travelers. In the Kingdom of Saudi Arabia (KSA), one case of EM was reported based on clinical suspicion with no laboratory confirmation; however, there have been no previous reported cases of Lyme disease in returning travelers. Here we present the first case in KSA in a healthy woman presenting with EM after returning from travel to Scotland, where the disease is endemic.